Summer School on Generic Programming - Backhouse, R (Springer−Verlag, 2003)
Generic programming is about making programming more effective by making it more general. This volume is about a novel form of genericity in programs, based on parameterizing programs by the structure of the data they manipulate. The material is based on lectures presented at a summer school on Generic Programming held at the University of Oxford in August 2002.